STUDY OF THE PREVALENCE OF ANEMIA IN PREGNANT WOMEN IN THE WORKING AREA OF COMMUNITY HEALTH CENTER X IN CENTRAL LOMBOK REGENCY - Srigede, Lalu Dio (Bajang Institute, 2025)
Abstract: Background: The mortality rate of anemia in pregnancy in Indonesia shows a fairly high value, namely (3.8%) in the first trimester, (13.6%) in the second trimester and (24.8%) in the third trimester. Pregnant women who are of unhealthy reproductive age are more likely to suffer from anemia than pregnant women who are of healthy reproductive age. Based on a preliminary study conducted in the working area of Puskesmas X, Central Lombok Regency, from January to August 2023, there were 45 cases of anemia in pregnant women. The purpose of this study was to determine the prevalence of anemia in pregnant women in the working area of Puskesmas X, Central Lombok Regency. Research Methods: This research design uses descriptive research with a cross-sectional approach. The population in this study was 45 people. The sampling used in this study was 100% according to the total population, namely 45 pregnant women suffering from anemia in the working area of Puskesmas X, Central Lombok Regency. Data collection techniques are secondary data by looking at the pregnant women's registration book, and data analysis using univariate analysis with frequency distribution and percentage. Results and Conclusions: The results of the study showed that of the 45 respondents, pregnant women who experienced anemia, in terms of maternal age characteristics, most were of healthy reproductive age (20-35 years), namely 32 people (71%). Then, in terms of gravida characteristics, most were primigravida, namely 30 people (67%). Then, for nutritional status characteristics, most had good nutritional status, namely 28 people (62%). Then, in terms of compliance with consuming iron tablets, most were not compliant with consuming iron tablets, namely 33 people (73%). Furthermore, in terms of socio-economic conditions, most were from lower to middle socio-economic conditions, namely 42 people (93%). Finally, in terms of education level, most came from secondary education, namely 29 people (64%).